(untitled) (Scientific journal of the Fergana State University, 2024)
This article philosophically reveals that existentialism can be called the philosophy of human life, the philosophy of life and the philosophy of tension, that the main thing that existentialists study is the meaning of a particular person’s life. In the first half of the 20th century, a scientific analysis of the essence of Existentialism was carried out, which acquired a new and special meaning.